Why are family carers of people with dementia dissatisfied with general hospital care?: a qualitative study - Jurgens, Fiona J.; Clissett, Philip; Gladman, John R.F.; Harwood, Rowan H. (BioMed Central, 2012)
Background Families and other carers report widespread dissatisfaction with general hospital care for confused older people.